Anti-micro-pitting wind power gear oil with particle size effect and preparation method thereof
Patent Information
- Application Number
- CN202611156629.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有研究尚未建立纳米颗粒粒径与表面粗糙度之间的定量匹配关系,导致其在抑制微点蚀方面的作用效果难以预测和控制
[0020](1) The present invention takes the quantitative matching relationship between the particle size of the nano-additive and the surface roughness of the friction pair as the core design basis for anti-micropitting performance. Through the dual particle size control criteria of Davg≤0.5×Ra and D90
Smart Images

Figure CN122917845A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lubricating oil, and particularly relates to a wind turbine gear oil. Background Technology
[0002] As wind power generation expands towards higher power outputs and deeper offshore applications, wind turbine gearboxes, as the core transmission components of wind turbines, face increasingly demanding operating conditions. Wind turbine gearboxes typically operate under complex conditions such as low-speed heavy loads, variable speed and load, and impact vibrations. Furthermore, due to the instability of wind energy, gearboxes frequently undergo start-stop and load changes, making it difficult to form a stable full oil film lubrication at the lubrication interface. Consequently, they often operate in a mixed lubrication or even boundary lubrication state. Under these conditions, the lubricating oil film thickness is insufficient to completely separate the meshing tooth surfaces, leading to direct contact between surface roughness peaks and localized stress concentration. Under cyclic stress, the material suffers fatigue damage, ultimately resulting in micron-sized fatigue spalling and pitting corrosion on the surface.
[0003] Micropitting, as one of the most common early failure modes in wind turbine gearboxes, poses a significant threat. On one hand, micropitting disrupts the integrity of the gear surface, increases surface roughness, further deteriorates lubrication, and creates a vicious cycle. On the other hand, stress concentration at the edges of micropitted pits can induce crack propagation, ultimately evolving into macropitting, abrasive wear, and even tooth breakage. Statistics show that micropitting has become one of the main causes of premature failure in wind turbine gearboxes, resulting in significant economic losses for the wind power industry. Therefore, wind turbine gear oils must possess excellent anti-micropitting properties, effectively protecting gear surfaces under mixed lubrication conditions and delaying or inhibiting the initiation and propagation of micropitting.
[0004] Traditional anti-micropitting technologies mainly rely on small-molecule sulfur-phosphorus additives to generate a protective film through tribochemical reactions. However, the friction film formed by these additives has limited thickness and insufficient strength, making it difficult to provide long-term protection under harsh operating conditions. In recent years, research on nanoparticles as lubricant additives has yielded fruitful results. Their unique "ball bearing effect" and "self-healing effect" provide a new technical path for improving lubrication performance. Studies have shown that whether nanoparticles can effectively fill surface micro-defects and form a continuous and dense protective film depends not only on the properties of the material itself but also on the relative scale relationship between their particle size and the surface roughness of the friction pair. However, existing research has not established a quantitative matching relationship between nanoparticle size and surface roughness, making it difficult to predict and control their effect in inhibiting micropitting. Therefore, how to precisely control the particle size distribution of nanoparticles to achieve a quantitative match with the surface roughness of gears, and how to synergize with additives during friction to form a composite lubricating film with sufficient strength and thickness in situ, thereby fundamentally inhibiting the initiation and spread of micropitting, has become a pressing technical problem to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing nano-lubrication technologies, such as the thin and low-strength friction films formed by anti-micropitting additives, which struggle to provide long-term protection for gear surfaces under mixed lubrication conditions, and the lack of particle size matching design tailored to gear surface characteristics, this invention proposes an anti-micropitting wind turbine gear oil with particle size effect and its preparation method. This gear oil achieves efficient micro-area filling by selecting copper nanoparticles of a specific particle size that matches the surface roughness characteristics of the friction pair. Under friction-induced synergy with thiophosphate, it constructs a strong and tough composite lubricating film in situ, fundamentally inhibiting the initiation and spread of micropitting.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0007] A wind turbine gear oil with particle size effect for resisting micropitting, comprising the following components by mass percentage: 0.5-2.0% copper nanoparticles, 0.5-3.0% thiophosphate, 0.1-0.5% antioxidant, 0.01-1.0% corrosion inhibitor, 0.1-0.5% demulsifier, 0.05-0.1% antifoaming agent, 0.5-1.5% dispersant, with the balance being base oil, and the sum of the mass percentages of the above components being 100%.
[0008] The copper nanoparticles are characterized by being spherical particles modified with oil-soluble organic ligands, with an average particle size D. avg Surface roughness R of the lubricated contact pair a Satisfying the relation: D avg ≤0.5×R a And D 90 <R a Meanwhile, the particle size distribution range of copper nanoparticles is 2-50 nm.
[0009] Preferably, the surface of the copper nanoparticles is modified with a modifier, which is a carboxylic acid, thiol, amine, silane coupling agent, phosphonic acid, or phosphate ester organic compound. The modifier is chemically adsorbed onto the copper core surface via ligands, and the modifier content is 5-70 wt%. The introduction of oil-soluble organic ligands not only improves the dispersion stability of the nanoparticles in the base oil but also endows them with good interfacial compatibility, which is beneficial for controlled release and directional transport during friction.
[0010] Preferably, the thiophosphate is one or more of the following: molybdenum dialkyl dithiophosphate, zinc dialkyl dithiophosphate, antimony dialkyl dithiophosphate, copper dialkyl dithiophosphate, lead dialkyl dithiophosphate, ammonium thiophosphate ester, or nitrogen-containing derivatives of thiophosphate; the alkyl structure is one or more combinations of primary alkyl, secondary alkyl, or aromatic groups having 2-22 carbon atoms.
[0011] Preferably, the base oil is a polyalphaolefin; more preferably, the base oil is a mixture of PAO10 and PAO40. PAO base oils have excellent viscosity-temperature properties, low-temperature fluidity, and thermal oxidation stability. By blending different viscosity grades, precise control of oil film thickness can be achieved.
[0012] Preferably, the antioxidant is an amine antioxidant and / or a phenolic antioxidant; the amine antioxidant is one or more of phenylenediamine, diphenylamine, N,N-dimethylaniline and alkylphenthiazine antioxidants; the phenolic antioxidant is one or more of hindered phenolic esters, thioether phenols and polycyclic hindered phenols.
[0013] Preferably, the preservative is one or more of the following: organic carboxylic acids, organic carboxylates, lipids, organic amines, sulfur-nitrogen heterocyclic compounds, and inorganic salts.
[0014] Preferably, the demulsifier is an alkylene diamine tetrapolyoxypropylene derivative and / or a polyethylene oxide / propylene oxide copolymer.
[0015] Preferably, the antifoaming agent is a polydimethylsiloxane and / or an acrylate copolymer.
[0016] Preferably, the dispersant is one or a mixture of succinimide, succinate, benzylamine, and ashless phosphate.
[0017] Furthermore, the copper nanoparticles and thiophosphate synergistically interact under friction-induced conditions to form a strong and tough composite lubricating film in situ at the friction interface. This composite lubricating film combines the rolling / filling effect of nanoparticles with the chemical reaction film characteristics of thiophosphate: the copper nanoparticles act as micro-balls and fill micro-defects in the contact area, while also serving as active sites to promote the tribochemical reaction of thiophosphate; the thiophosphate decomposes under frictional heat and shear force, generating a tribochemical reaction film that forms a composite structure with the nanoparticles, significantly improving load-bearing capacity and resistance to rolling contact fatigue.
[0018] The present invention further provides a method for preparing the above-mentioned anti-micropitting wind turbine gear oil, comprising the following steps: under normal temperature conditions, base oil, thiophosphate, antioxidant, corrosion inhibitor, deemulsifier, antifoaming agent and dispersant are added to a mixing vessel equipped with a stirrer in mass percentage, and stirred for 1-2 hours until the mixture is uniform; then copper nanoparticles are added, and stirring is continued for 1-2 hours until the mixture is uniform and transparent, thereby obtaining the anti-micropitting wind turbine gear oil.
[0019] The beneficial effects of this invention are:
[0020] (1) The present invention takes the quantitative matching relationship between the particle size of the nano-additive and the surface roughness of the friction pair as the core design basis for anti-micropitting performance. Through the dual particle size control criteria of Davg≤0.5×Ra and D90<Ra, it is ensured that the vast majority of nanoparticles can effectively enter the micro-defect area of the friction surface, directly reduce the contact stress of micro-asperities through the micro-area filling effect, block the initiation path of micro-cracks, and avoid the risk of abrasive wear caused by large-sized particles at the same time.
[0021] (2) In the present invention, copper nanoparticles are modified with oil-soluble organic ligands, so that they have good dispersion stability in base oil and are not prone to agglomeration. During the friction process, the small-sized copper nanoparticles have high specific surface area and strong surface activity, which can not only undergo plastic deformation and spread on the friction interface, but also act as active sites to promote the tribochemical reaction of thiophosphates. The two act synergistically on the friction interface to form a strong and tough composite lubricating film in situ. The crystal phase of copper nanoparticles is uniformly distributed inside the composite lubricating film, which combines the easy-shear property of copper material and the high load-bearing capacity of the thiophosphate reaction film. The thickness and strength of the formed film are significantly better than the nanoscale film formed by a single additive. The formation of the composite lubricating film can effectively reduce the plastic deformation of the surface layer and subsurface layer of the metal material, reduce the accumulation of shear stress, and improve the anti-micropitting performance from two aspects of film forming quality and stress distribution.
[0022] (3) Based on the synergistic effect of nanoparticles and thiophosphates, the anti-micropitting wind turbine gear oil of the present invention can fundamentally inhibit the initiation and propagation of micropitting, has strong in-situ film forming ability, high load-bearing capacity, excellent friction-reducing and anti-wear performance, is especially suitable for equipment under low-speed heavy-load and mixed lubrication conditions such as wind turbine gearboxes, and can provide long-term lubrication protection. Brief Description of the Drawings
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention or the prior art, the following will briefly introduce the accompanying drawings that need to be used in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, on the premise of no creative work, other drawings can also be obtained based on these drawings.
[0024] Figure 1 are the transmission electron microscope image (a) and the particle size distribution statistical diagram (b) of the oleic acid-modified copper nanoparticles used in Example 1 of the present invention.
[0025] Figure 2 is the XRD pattern of the oleic acid-modified copper nanoparticles used in Example 1 of the present invention.
[0026] Figure 3 are the transmission electron microscope image (a) and the particle size distribution statistical diagram (b) of the acetic acid-modified copper nanoparticles used in Comparative Example 4 of the present invention.
[0027] Figure 4 The graph (a) shows the friction coefficient variation over time when the samples of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention are used as lubricants, and the graph (b) shows the comparison of the average friction coefficient.
[0028] Figure 5 The image shows a comparison of the wear volume of the steel disc wear marks after testing with an SRV friction and wear tester when the samples of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention were used as lubricants. The image also shows a side view of the wear mark depth.
[0029] Figure 6 The images show top views (a1-a5) and side views (b1-b5) of the wear marks on the steel discs after testing with an SRV friction and wear tester when the samples of Examples 1, 1, 2, 3 and 4 of this invention were used as lubricants. Detailed Implementation
[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Preparation method of copper nanoparticles
[0032] The copper nanoparticles modified with the oil-soluble modifier used in the following examples can be prepared by a solvothermal method or a liquid-phase reduction method. The specific steps are described below using the solvothermal method as an example: Weigh 0.005 mol of copper oleate into a three-necked flask, add 5 mL of oleylamine, and magnetically stir for 10 min at room temperature to ensure thorough mixing. Then, heat to 50°C and continue stirring for 20 min. Add 0.005 mol of anhydrous glucose to the reaction system and stir continuously for 15 min under nitrogen protection to ensure uniform dispersion of the reactants. Then, slowly raise the system temperature to 230°C and stir at this constant temperature for 2 h. After the reaction is complete, allow it to cool naturally to room temperature. Wash the obtained product three times with anhydrous ethanol, centrifuge at 10,000 rpm for 15 min, collect the precipitate, and vacuum dry at 30°C for 12 h to obtain the copper nanoparticles modified with the oleic acid modifier.
[0033] Performance testing methods
[0034] The anti-micropitting performance of wind turbine gear oil was evaluated using an SRV-5 friction and wear tester (ball-disc contact configuration). Both the ball and disc were made of bearing steel. The lower sample was a disc with a diameter of 24 mm and a thickness of 7.9 mm. The average surface roughness R... a = 25 ± 0.03 nm, hardness HRC 60 ± 2; the upper sample is a steel ball with a diameter of 10 mm and an average surface roughness R a = 50 nm, hardness HRC 63 ± 2. Typical micropitting test conditions are: temperature 75℃, frequency 25 Hz, amplitude 5mm, stepped loading program starting from 50 N, increasing in increments of 100 N to 350 N, with each load lasting 30 min, and a total test duration of 2 h.
[0035] Example 1
[0036] Based on parts by weight, the total number of parts is 100, including 2.0 parts of oleic acid-modified copper nanoparticles (D...) with an average particle size of 10.2 nm. 90 1.5 parts of zinc dialkyl dithiophosphate (ZDDP), 0.3 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.1 parts of preservative barium dinonylnaphthalenesulfonate, 0.3 parts of antiemulsifier amine-epoxide condensate, 0.05 parts of antifoaming agent acrylate copolymer, 1.0 part of dispersant polyisobutylene succinimide, and the balance of blending base oil (PAO10 and PAO40 blended in a mass ratio of 1:9) were added to a mixing vessel equipped with a stirrer and stirred at room temperature for 2 hours until the mixture was uniform, transparent, and reddish-brown, thus obtaining the anti-micropitting wind turbine gear oil.
[0037] In this embodiment, the average particle size D of the copper nanoparticles avg =10.2 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×R a And D 90 =15.3 nm < Ra, which meets the particle size matching requirements of this invention.
[0038] Comparative Example 1 (Blank Example)
[0039] The total weight is 100 parts. 0.3 parts of antioxidant (2,6-di-tert-butyl-p-cresol, T501), 0.1 parts of preservative (barium dinonylnaphthalenesulfonate, T705), 0.3 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.1 parts of preservative barium dinonylnaphthalenesulfonate, 0.3 parts of demulsifier amine-epoxide condensate, 0.05 parts of antifoaming agent acrylate copolymer, 1.0 part of dispersant polyisobutylene succinimide, and the balance blending base oil (PAO10 and PAO40 blended in a 1:9 mass ratio) are added to a mixing vessel equipped with a stirrer and stirred at room temperature for 2 hours until homogeneous to obtain the lubricating oil. This comparative example does not contain copper nanoparticles or thiophosphates.
[0040] Comparative Example 2 (Single Copper Nanoparticle Example)
[0041] The total amount of 100 parts by weight is as follows: 2.0 parts of oleic acid-modified copper nanoparticles with an average particle size of 10.2 nm, 0.3 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.1 parts of preservative barium dinonylnaphthalenesulfonate, 0.3 parts of demulsifier amine-epoxide condensate, 0.05 parts of antifoaming agent acrylate copolymer, 1.0 part of dispersant polyisobutylene succinimide, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9) are added to a mixing vessel equipped with a stirrer and stirred at room temperature for 2 hours until homogeneous to obtain the lubricating oil. This comparative example does not contain thiophosphate.
[0042] Comparative Example 3 (Monothiophosphate Example)
[0043] The total weight is 100 parts. 1.5 parts of thiophosphate (T307), 0.3 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.1 parts of preservative barium dinonylnaphthalenesulfonate, 0.3 parts of demulsifier amine-epoxide condensate, 0.05 parts of antifoaming agent acrylate copolymer, 1.0 part of dispersant polyisobutylene succinimide, and the balance base oil (PAO10 and PAO40 blended in a 1:9 mass ratio) are added to a mixing vessel equipped with a stirrer and stirred at room temperature for 2 hours until homogeneous to obtain the lubricating oil. This comparative example does not contain copper nanoparticles.
[0044] Comparative Example 4 (Example of large-diameter microparticles)
[0045] Based on parts by weight, the total number of parts is 100, and 2.0 parts of acetic acid-modified copper nanoparticles with an average particle size of approximately 47.8 nm are included. 90The following ingredients were added to a mixing vessel equipped with a stirrer: 58.3 nm thick phosphate (T307), 1.5 parts thiophosphate (T307), 0.3 parts antioxidant 2,6-di-tert-butyl-p-cresol, 0.1 parts preservative barium dinonylnaphthalenesulfonate, 0.3 parts antiemulsifier amine-epoxide condensate, 0.05 parts antifoaming agent acrylate copolymer, 1.0 part dispersant polyisobutylene succinimide, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9). The mixture was stirred at room temperature for 2 hours until homogeneous.
[0046] In this comparative example, the average particle size D of the copper nanoparticles avg =47.8 nm, and the surface roughness R of the friction pair a The matching relationship at 25 nm does not satisfy D. avg ≤ 0.5×R a And D 90 =58.3 nm > Ra, which does not meet the particle size matching requirements of this invention.
[0047] Performance testing and evaluation:
[0048] 1. Synthesis and characterization of copper nanoparticles with different particle sizes
[0049] Figure 1 The microstructure and particle size distribution characteristics of the oleic acid-modified copper nanoparticles used in Example 1 of this invention are shown. Figure 1 (a) is a transmission electron microscope image. Figure 1 (b) shows the corresponding particle size distribution statistics. Figure 1 (a) It can be seen that the prepared copper nanoparticles exhibit a regular spherical morphology and uniform particle size, without agglomeration. Figure 1 (b) The statistical results show that the D of the nanoparticles avg It is 10.2 nm, D 90 The particle size is 15.3 nm. This particle size characteristic satisfies the core matching relationship proposed in this invention: D avg ≤0.5×R a And D 90 < R a This is the foundation for the subsequent effective entry of nanoparticles into the micro-defects on the surface of the friction pair to achieve the "micro-area filling effect," and is the technical prerequisite for the present invention to achieve resistance to micro-pitting corrosion.
[0050] Figure 2 The XRD pattern of the oleic acid-modified copper nanoparticles used in Example 1 is shown. As can be seen from the figure, three characteristic diffraction peaks appear at 2θ = 43.3°, 50.4°, and 74.1°, corresponding to the (111), (200), and (220) crystal planes of face-centered cubic copper, respectively. No diffraction peaks of oxides such as CuO or Cu₂O were detected in the pattern.
[0051] Figure 3 The images shown are transmission electron microscopy (TEM) images (a) and particle size distribution statistics (b) of the acetic acid-modified copper nanoparticles used in Comparative Example 4 of this invention. This sample serves as a comparative example that does not meet the particle size matching requirements of this invention. Figure 1 compared to, Figure 3 Although the copper nanoparticles shown are also spherical, their particle size is significantly increased, D avg Approximately 47.8 nm, D 90 The particle size is 58.3 nm. This particle size characteristic does not meet the matching requirements of this invention. The excessively large particle size prevents it from entering most surface micro-valves, and may instead act as a "micro-protrusion" at the friction interface, causing localized stress concentration or abrasive wear.
[0052] 2. Test results of friction reduction, wear resistance, and micropitting resistance.
[0053] Figure 4 The figures (a) and (b) show the friction coefficient variation curves (b) and average friction coefficient comparisons (b) of Examples 1, 1, 2, 3, and 4 of this invention in the SRV friction and wear test. The results show that Example 1 has the most stable friction coefficient curve and the lowest average friction coefficient, significantly lower than Comparative Examples 2, 3, and 4. This indicates that the combined use of small-diameter copper nanoparticles and thiophosphate (Example 1) produces a significant synergistic friction-reducing effect, far exceeding the effect of simple superposition of single additive components. Furthermore, the friction-reducing effect of small-diameter copper nanoparticles (Example 1) that satisfy the matching relationship is significantly better than that of large-diameter particles (Comparative Example 4) that do not satisfy the matching relationship. The effective reduction in friction coefficient directly reduces the accumulation of shear stress on the surface and subsurface of the tooth surface, which is one of the key mechanical factors in inhibiting the initiation of micropitting corrosion.
[0054] Figure 5 The comparison of wear volume (a) and wear track depth profile (b) of the specimens (steel discs) of Example 1 and various comparative examples after the SRV test is shown. The results show that Example 1 exhibits the smallest wear volume and the shallowest wear track depth among all samples. This result further verifies the effectiveness of the technical solution of the present invention from the perspective of anti-wear performance. The significant reduction in wear volume and depth is directly attributed to the strong and tough composite lubricating film formed in situ at the friction interface. This composite film effectively isolates the direct contact between the friction pairs, slows down the plastic deformation and removal of materials, provides long-term protection for the gear surface, and delays the evolution of micropitting corrosion from the perspective of material loss.
[0055] The three-dimensional morphology of the wear tracks on the steel discs of Examples 1, 1, 2, 3, and 4, used as lubricants, after testing with an SRV tribological testing machine, is shown in top view (a1-a5) and side view (b1-b5). This experiment simulates the rolling contact fatigue process of a wind turbine gearbox under variable speed and load conditions by gradually increasing the load, and is used to directly evaluate the anti-micropitting performance of each oil sample. The results show that Example 1 (copper nanoparticles with matching particle size + thiophosphate), as shown in Figures a1 and b1, has the smoothest and flattest wear track surface among all samples, with no micropitting pits or fatigue spalling observed, and the smallest wear volume. This result fully verifies the effectiveness of the core technical solution of this invention: copper nanoparticles that meet the matching relationship of Davg ≤ 0.5×Ra and D90 < Ra can accurately fill surface micro-defects and, under friction induction, act as active sites to promote the tribochemical reaction of thiophosphate. The two work together to form a strong and tough composite lubricating film in situ at the friction interface. This composite film possesses both excellent load-bearing capacity and fatigue resistance, fundamentally blocking the initiation and propagation path of micropitting corrosion, and achieving a synergistic effect that cannot be achieved by a single additive component.
[0056] Comparative Example 1, as shown in the top view (a2) and side view (b2), exhibits micropitting at the wear track site under the lubrication of the basic formulation of copper nanoparticles and thiophosphate. Comparative Example 2 (with only copper nanoparticles matching the particle size), as shown in Figures a3 and b3, shows no obvious micropitting on the wear track surface, and the wear volume is significantly smaller than that of Comparative Examples 1 and 3. This result demonstrates that copper nanoparticles matching the particle size can effectively reduce the contact stress of micro-protrusions through the "micro-area filling effect," inhibiting the initiation of micropitting at its source, and its anti-micropitting effect is superior to that of traditional thiophosphate alone. However, due to the lack of synergistic enhancement from the chemical reaction film of thiophosphate, its wear volume is larger than that of Example 1. Comparative Example 3 (with only thiophosphate added): as shown in Figures a4 and b4, only a very small number of micropittings are observed on the wear track surface, and the wear volume is smaller than that of Comparative Example 1. This indicates that the protective film formed by traditional thiophosphate additives through tribochemical reactions has a certain resistance to micropitting corrosion. However, due to the limited film thickness, it is still difficult to completely resist the cumulative damage of cyclic shear stress when subjected to stepped loading to higher loads. Comparative Example 4 (large-diameter copper nanoparticles + thiophosphate), as shown in Figures a5 and b5, shows a large number of micropits on the wear surface, accompanied by deep furrows, and the wear volume is significantly increased. This result indicates that when the average particle size of copper nanoparticles is much larger than the surface roughness, the large-diameter particles not only cannot effectively enter the surface micro-valves to fill them, but also act as "abrasive particles" to exacerbate surface damage. Even with the addition of thiophosphate, it is difficult to compensate for the performance degradation caused by the particle size mismatch.
[0057] Example 2
[0058] Based on parts by weight, the total number of parts is 100, including 1.5 parts of oleic acid-modified copper nanoparticles (D...) with an average particle size of 10.2 nm. 90 The following ingredients were added to a mixing vessel equipped with a stirrer: 1.0 part zinc dialkyl dithiophosphate (ZDDP), 0.3 part diphenylamine antioxidant, 0.5 part benzotriazole preservative, 0.3 part polyethylene oxide / propylene oxide copolymer demulsifier, 0.06 part polydimethylsiloxane antifoaming agent, 0.8 part succinate dispersant, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9). The mixture was stirred at room temperature for 2 hours until the mixture was uniform, transparent, and reddish-brown, thus obtaining the anti-micropitting wind turbine gear oil.
[0059] In this embodiment, the average particle size D of the copper nanoparticles avg =10.2 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×R a And D 90 =15.3 nm < Ra, which meets the particle size matching requirements of this invention.
[0060] Example 3
[0061] Based on parts by weight, the total number of parts is 100, including 1.0 part of dodecyl mercaptan-modified copper nanoparticles (D) with an average particle size of 8.6 nm. 90 12.4 nm), 2.5 parts of molybdenum dialkyl dithiophosphate (MoDDP), 0.4 parts of alkylphenthiazide antioxidant, 0.3 parts of thiadiazole derivative preservative, 0.4 parts of alkylene diamine tetrapolyoxypropylene derivative demulsifier, 0.07 parts of acrylate copolymer antifoaming agent, 1.2 parts of ashless phosphate dispersant, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9) were added to a mixing vessel with a stirrer and stirred at room temperature for 2 hours until the mixture was homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0062] In this embodiment, the average particle size D of the copper nanoparticles avg =8.6 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×Ra, and D 90 =12.4 nm < Ra, which meets the particle size matching requirements of this invention.
[0063] Example 4
[0064] By weight, the total number of parts is 100, and 0.5 parts of stearic acid-modified copper nanoparticles (D) with an average particle size of 12.6 nm are included. 90The following ingredients were added to a mixing vessel equipped with a stirrer: 18.3 nm, 2.0 parts of zinc dialkyl dithiophosphate (ZDDP), 0.2 parts of diphenylamine antioxidant, 0.5 parts of benzotriazole preservative, 0.2 parts of polyethylene oxide / propylene oxide copolymer demulsifier, 0.08 parts of polydimethylsiloxane antifoaming agent, 0.8 parts of succinate dispersant, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9). The mixture was stirred at room temperature for 2 hours until homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0065] In this embodiment, the average particle size D of the copper nanoparticles avg =12.6 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×R a And D 90 =18.3 nm < Ra, which meets the particle size matching requirements of this invention.
[0066] Example 5
[0067] Based on parts by weight, the total number of parts is 100, including 1.5 parts of oleic acid-modified copper nanoparticles (D...) with an average particle size of 10.2 nm. 90 15.3 nm), 2.5 parts of molybdenum dialkyl dithiophosphate (MoDDP), 0.4 parts of alkylphenthiazide antioxidant, 0.3 parts of thiadiazole derivative preservative, 0.4 parts of alkylene diamine tetrapolyoxypropylene derivative demulsifier, 0.06 parts of acrylate copolymer antifoaming agent, 1.2 parts of ashless phosphate dispersant, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9) were added to a mixing vessel with a stirrer and stirred at room temperature for 2 hours until the mixture was homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0068] In this embodiment, the average particle size D of the copper nanoparticles avg =10.2 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×R a And D 90 =15.3 nm < Ra, which meets the particle size matching requirements of this invention.
[0069] Example 6
[0070] Based on parts by weight, the total number of parts is 100, and 1.2 parts of silane coupling agent KH-550 with an average particle size of 18.5 nm are used to modify copper nanoparticles (D... 902.0 parts of zinc dialkyl dithiophosphate (ZDDP), 0.3 parts of alkylphenthiazide antioxidant, 0.6 parts of benzotriazole preservative, 0.3 parts of amine and epoxide condensate demulsifier, 0.07 parts of acrylate copolymer antifoaming agent, 1.3 parts of ashless phosphate dispersant, and the balance base oil (PAO10 and PAO40 blended at a mass ratio of 1:9) were added to a mixing vessel with a stirrer and stirred at room temperature for 2 hours until the mixture was homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0071] In this embodiment, the average particle size D of the copper nanoparticles avg =18.5 nm, and the surface roughness R of the friction pair a The matching relationship of 50 nm satisfies D avg ≤ 0.5×Ra, and D 90 =26.3 nm < Ra, which meets the particle size matching requirements of this invention.
[0072] Example 7
[0073] By weight, the total number of parts is 100, and 0.5 parts of di(2-ethylhexyl)phosphate-modified copper nanoparticles (D) with an average particle size of 6.5 nm are included. 90 The following ingredients are added to a mixing vessel equipped with a stirrer: 1.5 parts of ammonium thiophosphate salt, 0.2 parts of polycyclic hindered phenol antioxidant, 0.01 parts of inorganic salt preservative (sodium nitrite), 0.4 parts of polyethylene oxide / propylene oxide copolymer demulsifier, 0.1 parts of polydimethylsiloxane antifoaming agent, 0.7 parts of benzylamine dispersant, and the balance base oil (PAO10 and PAO40 blended in a mass ratio of 1:9). The mixture is stirred at room temperature for 1.5 hours until homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0074] In this embodiment, the average particle size Da of the copper nanoparticles vg =12.6 nm, and the surface roughness R of the friction pair a The matching relationship of 25 nm satisfies D avg ≤ 0.5×R a And D 90 =18.3 nm < R a This meets the particle size matching requirements of the present invention.
[0075] Example 8
[0076] Based on parts by weight, the total number of parts is 100, and 1.2 parts of silane coupling agent KH-550 with an average particle size of 18.5 nm are used to modify copper nanoparticles (D... 902.0 parts of dialkyl dithiophosphate lead (PbDDP), 0.3 parts of alkylphenthiazide antioxidant, 0.6 parts of benzotriazole preservative, 0.3 parts of amine and epoxide condensate demulsifier, 0.07 parts of acrylate copolymer antifoaming agent, 1.3 parts of ashless phosphate dispersant, and the balance base oil (PAO10 and PAO40 in a mass ratio of 1.5:8.5) were added to a mixing vessel with a stirrer and stirred at room temperature for 2 hours until the mixture was homogeneous to obtain the anti-micropitting wind turbine gear oil.
[0077] In this embodiment, the average particle size D of the copper nanoparticles avg =18.5 nm, and the surface roughness R of the friction pair a The matching relationship of 50 nm satisfies D avg ≤ 0.5×R a And D 90 =26.3 nm < R a This meets the particle size matching requirements of the present invention.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A wind turbine gear oil with particle size effect for preventing micropitting, characterized in that, The product comprises, by mass percentage, the following components: 0.5-2.0% copper nanoparticles, 0.5-3.0% thiophosphate, 0.1-0.5% antioxidant, 0.01-1.0% preservative, 0.1-0.5% deemulsifier, 0.05-0.1% antifoaming agent, and 0.5-1.5% dispersant, with the balance being base oil. The sum of the mass percentages of all components is 100%. The copper nanoparticles are spherical particles with surfaces modified by oil-soluble organic ligands. The particle size distribution range of the copper nanoparticles is 2-50 nm, and their average particle size Davg satisfies the relationship between Davg and the surface roughness Ra of the lubricating contact pair: Davg ≤ 0.5 × Ra, and D ≥ 90. <Ra。 2. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The oil-soluble organic ligand is one or more of the following: carboxylic acids, thiols, amines, silane coupling agents, phosphonic acids, and phosphate esters; the organic ligand is bound to the surface of copper nanoparticles by chemical adsorption, and the mass of the organic ligand accounts for 5-70% of the total mass of the copper nanoparticles.
3. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The thiophosphate is one or more of the following: dialkyl molybdenum dithiophosphate, dialkyl zinc dithiophosphate, dialkyl antimony dithiophosphate, dialkyl copper dithiophosphate, dialkyl lead dithiophosphate, ammonium thiophosphate ester, and nitrogen-containing derivatives of thiophosphate; the alkyl structure is one or more combinations of primary alkyl, secondary alkyl, or aromatic groups having 2-22 carbon atoms.
4. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The base oil is a polyalphaolefin.
5. The wind turbine gear oil with particle size effect according to claim 4, characterized in that, The base oil is a mixture of PAO10 and PAO40.
6. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The antioxidant is an amine antioxidant and / or a phenolic antioxidant; the amine antioxidant is one or more of phenylenediamine, diphenylamine, N,N-dimethylaniline and alkylphenthiazides; the phenolic antioxidant is one or more of hindered phenolic esters, thioether phenols and polycyclic hindered phenols.
7. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The preservative is one or more of the following: organic carboxylic acids, organic carboxylate salts, lipids, organic amines, sulfur-nitrogen heterocyclic compounds, and inorganic salts.
8. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The demulsifier is an alkylene diamine tetraoxypropylene derivative and / or a polyethylene oxide-propylene oxide copolymer.
9. The wind turbine gear oil with particle size effect according to claim 1, characterized in that, The antifoaming agent is a polydimethylsiloxane and / or an acrylate copolymer; the dispersant is one or more of succinimide, succinate, benzylamine, and ashless phosphate.
10. The method for preparing the anti-micropitting wind turbine gear oil with particle size effect according to any one of claims 1-9, characterized in that, The process includes the following steps: at room temperature, the base oil, thiophosphate, antioxidant, preservative, deemulsifier, antifoaming agent and dispersant are mixed evenly according to their mass percentages; then copper nanoparticles are added and stirred evenly to obtain the anti-micropitting wind turbine gear oil.